Effect of Addition of Green Spinach Extract (Amaranthus hybridus L.) on the Chemical and organoleptic Characteristics of Yellow Sweet Potato Sticks - Safira Sangadji; Rachel Breemer; Meitycorfrida Mailoa (Jurnal Agrosilvopasture-Tech, 2023)
Sticks are snacks or a type of pastry that people like, long, flat, crunchy in texture and taste good. People often consume sticks as a daily snack, ranging from children, adolescents and adults (Nurwahidah, 2019). The purpose of this study was to determine the appropriate green spinach extract on the chemical and organoleptic characteristics of yellow sweet potato sticks. This research uses a complete randomized design (RAL) single factor that is the weight of green spinach made into extracts with 4 levels of treatment as follows : P0 = spinach 0 g, P1 = spinach 100 g, P2 = spinach 200 g and P3 = spinach 300 g. The results of yellow sweet potato sticks 300 g spinach green treatment is the best treatment based on chemical characteristics include water content (5.64%), ash content (3.27%), Protein content (8.77%), fat content (21.67%), crude fiber content (1.95%) and carbohydrate content (58.65%), in addition to the treatment of organoleptic test on 300 g treatment is also the best treatment of hedonic and hedonic spinach taste (3,08) like, texture (3,20) crunchy (3,04) like, color (2.95) and overall (3.08) likes.